Battered women: implications for social control - Davis, Nanette J. (Contemporary crises, 1988)
This paper examines battered women as a systemic problem of social control, involving three structural phases: structure, deconstruction and reconstruction. At the first phase, woman battering occurs in a context of dependency, including economic, social, political, and emotional subordination that maintains the traditional, male-centered family structure. During phase two, or deconstruction, broad societal changes, including the feminist movement, contributes to altered gender definitions and the emergence of a battered women's movement and practice. During this phase feminists served as the chief reform catalyst, introducing protective legislation, educating the public and organizing women's shelters. Phase three, reconstruction, entails the state's direct involvement in the violent relationship in a series of coercive netwidening actions, including arrest of the offender, forcible separation of the couple, and formal sentencing. On the one hand, state intervention substantially reduces the incidence of violence against women in the home. On the other hand, the power of arrest and detention extends state power into new spheres, as the state exploits social problems and weakened social structures in line with its expanding control agenda. Overbureaucratization during this phase also affects feminist practice, as shelters increasingly take on a social provision, sometimes anti-feminist, orientation that further constrains who can be served. The paper raises questions about the extent to which the reconstruction phase, operating in the interests of dominant groups, contributes to the revictimization of battered women.